The Cost of Migrating to a Culturally Different Location - Jens Ruhose; Oliver Falck; Alfred Lameli (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Ever since Sjaastad (1962), researchers have struggled to quantify the psychic cost of migration. We monetize psychic cost as the wage premium for moving to a culturally different location. We combine administrative social security panel data with a proxy for cultural difference based on unique data on historical dialect dissimilarity between German counties. Conditional on geographic distance and pre-migration wage profiles, we find that migrants demand a wage premium of about 1 percent for overcoming one standard deviation in cultural dissimilarity. The effect is driven by males, more pronounced for geographically short moves, and persistent over time.
Keywords: D51; J61; R23; 330